Answer:
x = 6, x = -5, x = 9
if f(x)=(x-6)(x+5)(x-9)
Explanation:
The zeros of a polynomial in factored form can be found by setting the polynomial equal to zero and then realizing if a product is zero, then at least one of it's factors is zero.
So we have the zero's are the x's that satisfy
(x-6)(x+5)(x-9)=0.
We just need to solve three equations:
x-6=0
This can be solved by adding 6 on both sides: x=6
x+5=0
This can be solved by subtracting 5 on both sides: x=-5
x-9=0
This can be solved by adding 9 on both sides: x=9
The solutions are in { 6,-5,9 }.